Purification, cloning, and primary structure of a new enantiomer-selective amidase from a Rhodococcus strain: structural evidence for a conserved genetic coupling with nitrile hydratase. - Mayaux, J F (1991)
A new enantiomer-selective amidase active on several 2-aryl propionamides was identified and purified from a newly isolated Rhodococcus strain. The characterized amidase is an apparent homodimer, each molecule of which has an Mr of 48,554; it has a specific activity of 16.5 mumol of S(+)-2-phenylpropionic acid formed per min per mg of enzyme from the racemic amide under our conditions. An oligonucleotide probe was deduced from limited peptide information and was used to clone the corresponding gene, named amdA. As expected, significant homologies were found between the amino acid sequences of the enantiomer-selective amidase of Rhodococcus sp., the corresponding enzyme from Brevibacterium sp. strain R312, and several known amidases, thus confirming the existence of a structural class of amidase enzymes. Genes probably coding for the two subunits of a nitrile hydratase, albeit in an inverse order, were found 39 bp downstream of amdA, suggesting that such a genetic organization might be conserved in different microorganisms. Although we failed to express an active Rhodococcus amidase in Escherichia coli, even in conditions allowing the expression of an active R312 enzyme, the high-level expression of the active recombinant enzyme could be demonstrated in Brevibacterium lactofermentum by using a pSR1-derived shuttle vector.